Pathways to Children's Behavioral Problems during the COVID-19 Pandemic: Fathers' Parenting Stress and Parenting Approaches - Fatma Ozge Ünsal; Ibrahim Hakki Acar (MDPI AG, 2023)
Although the family stress model theoretically focuses on the roles of both mothers and fathers as predictors of children's outcomes, studies generally have focused on mothers. The pandemic has brought additional burdens to parents' daily functioning, including fathers' involvement in childcare. The current study aimed to examine the contributions of fathers' parenting stress and parenting approaches to their children's behavior problems during the COVID-19 pandemic. Particularly, we examined the indirect effects of parenting stress on children's behavior problems via parenting practices. The participants were 155 fathers (Mage = 36.87, SD = 5.11) and their children (71 girls, 84 boys; Mage = 59.52, SD = 14.98) from Turkish contexts. The fathers reported their parenting stress, approaches, and children's behavioral problems. The results from the path analysis showed that parenting stress predicted children's internalizing and externalizing behaviors. Parenting stress also predicted severe punishment and obedience as parts of the parenting approach. Finally, parenting stress was indirectly related to children's externalizing behaviors via the punishment-based parenting approach of fathers. The findings of the current study highlighted the importance of examining the roles of fathers during the COVID-19 pandemic. Intervention programs targeting reducing fathers' parenting stress and negative parenting approaches would also be beneficial for reducing children's behavioral problems.